The Post-agencification Stage between Reforms and Crises. A Comparative Assessment of EU agencies' Budgetary Development - Marta Migliorati (JCMS: Journal of Common Market Studies, 2020)
The proliferation of European Union (EU) agencies, known as `agencification', has been widely studied by scholars of EU governance. In spite of the success in explaining the roots of agencies' establishment, evidence is lacking about their development over time: have they been empowered through new resources, or have their capabilities remained the same? Which EU agencies grew the most, and why? Ultimately, how much do policymakers value these bodies? Through a newly collected longitudinal dataset, the analysis covers EU agencies' budgetary trends in the past three decades and assesses the determinants of their variation through a cross-sectional time series regression analysis and a Traj group-based model. The results show that trends in agencies' budgetary allocation follow a punctuated equilibrium pattern. The observed variation is explained by EU-level crisis response, by the expansion of agencies' tasks and by the type of agency under analysis.
Keywords: 330; EU agencies; agencification; budget; EU governance